ChemInform Abstract: Catalytic C(sp3)—H Arylation of Free Primary Amines with an exo Directing Group Generated in situ. Issue 51 (5th December 2016) - Xu, Yan; Young, Michael C.; Wang, Chengpeng; Magness, David M.; Dong, Guangbin
Abstract: A range of aliphatic primary amines are site‐selectively arylated in the γ‐position using diaryl iodonium salts, and the products are isolated as the N‐benzoylated derivatives in moderate to high yields.